Iklan
Iklan

Penjelasan dengan langkah-langkah:

h(x) = 4 - 3x

h(2) = 4 - 3(2)

h(2) = 4 - 6

h(2) = -2

____________

h(x) = 4 - 3x

h(-3) = 4 - 3(-3)

h(-3) = 4 - (-9)

h(-3) = 4 + 9

h(-3) = 13

h(2) + h(-3)

= (-2) + 13

= 13 - 2

= 11

Iklan
Iklan

Hi, Nice2MeetU, let me help you ;)

________________________________

Diketahui

  • h(x) = 4 - 3x

Ditanya

  • h(2) + h(-3)

Dijawab

h(x) = 4 - 3x

h(2) = 4 - 3(2)

      = 4 - 6

      = -2

______________

h(x) = 4 - 3x

h(-3) = 4 - 3(-3)

       = 4 + 9

       = 13

______________

h(2) + h(-3)

= -2 + 13

{{\huge{\blue{\boxed{\tt{=11}}}}}}

{{\huge{\purple{\boxed{\boxed{\pink{\mathfrak{-Semoga\:Membantu-}}}}}}}}

Iklan
Iklan